Hubungan Kepatuhan Pengobatan Dengan Kualitas Hidup Pasien Gagal Ginjal Kronik Disertai Hipertensi dan Menjalani Hemodialisis - Agustina Nila Yuliawati; Pande Made Desy Ratnasari; I Gusti Ayu Santhi Pratiwi (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
End-stage renal disease (ESRD) patients undergoing hemodialysis (HD) could experience several problems, then reducing their quality of life (QOL). Medication adherence (MA), including HD is very important to improve the patient's QOL. This study aimed to analyze the correlation between MA and QOL and its related factors in ESRD patients. This cross-sectional study was conducted at a Public Hospital, Buleleng, Bali in September 2020. A sample of 89 people was obtained by the purposive sampling technique. The inclusion criteria for this study were ESRD patients aged ≥18 years, undergoing HD, filling out the questionnaire completely, and being able to communicate well. Data were collected using ERSD-AQ and EQ-5D-5L questionnaire, also medication records. Data analysis were performed by Perason’s rank correlation, Spearman’s rho, Kendall’s tau-b/c, Mann-Whitney U, or Kruskal Wallis test (CI 95%). Findings showed that mostly respondents were <60 years old (66.3%), male (71.9%), less than high school educational (68.5%), not working (69.7%), lower income (55.1%), having an ESRD duration of <3 years (67.4%), taking ≤6 item medicines (96.6%), having a mean (±SD) QOL-based on a utility value of 0.779±0.172 and a visual analog scale (VAS) of 60.79±18.04. Hence, there was no significant correlation between MA and QOL, as well as patient characteristics to MA (p>0.05).). Otherwise, patients aged <60 years, high levels of education and income, as well as the number of drug items received, tend to have a better QOL (p<0.05).